Four-Dimensional Painlevé-Type Equations Associated with Ramified Linear Equations III: Garnier Systems and Fuji-Suzuki Systems - Kawakami, H. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
This is the last part of a series of three papers entitled ''Four-dimensional Painlevé-type equations associated with ramified linear equations''. In this series of papers we aim to construct the complete degeneration scheme of four-dimensional Painlevé-type equations. In the present paper, we consider the degeneration of the Garnier system in two variables and the Fuji-Suzuki system.